Researches on ichthyofauna in the Natura 2000 sites from Banat (Romania) - OŢEL Vasile; NĂSTASE Aurel (Scientific Annals of the Danube Delta Institute, 2010)
In the autumn 2008 ichthyofauna was investigated in 3 Natura 2000 sites: Cheile Nera-Beuşniţa (Nera river and Miniş valley), Cheile Semenic –Caraş (Caras valley) and Timiş Meadow (Timiş river). The status of fish species of community interest (An. II / H.D.) inside of ichthyocenoses, as abundance and frequency, anthropogenicimpact, were assessed. In all 3 sites it were recorded 9 species of community interest (Aspius aspius, Barbus balcanicus, Cobitis elongata, Cottus gobio, Gobio kessleri, Gymnocephalus schraetzer, Rhodeus amarus, Sabanejewia balcanica, Zingel streber) in comparison with the reference lists which contain 15 species. Barbus balcanicus was a dominating species (as abundance and biomass) in the investigated area of Nera river, Miniş and Caraş valley. Cobitis elongata was found only in Nera river and probably this is the only place of Romania where it lives nowadays. Gymnocephalus schraetzer were collected by us in Timiş river and has to be added in the reference list of Timiş Meadow site. A main anthropogenic pressureconsists in the building of dams in all investigated water bodies, which stops the fish movement at the normal water levels.